Raman Spectroscopy of DLC/a-Si Bilayer Film Prepared by Pulsed Filtered Cathodic Arc. (1st November 2012) - Srisang, C.; Asanithi, P.; Siangchaew, K.; Limsuwan, S.; Pokaipisit, A.; Limsuwan, P.
Abstract : DLC/a-Si bilayer film was deposited on germanium substrate. The a-Si layer, a seed layer, was firstly deposited on the substrate using DC magnetron sputtering and DLC layer was then deposited on the a-Si layer using pulsed filtered cathodic arc method. The bilayer films were deposited with different DLC/a-Si thickness ratios, including 2/2, 2/6, 4/4, 6/2, and 9/6. The effect of DLC/a-Si thickness ratios on the sp 3 content of DLC was analyzed by Raman spectroscopy. The results show that a-Si layer has no effect on the structure of DLC film. Furthermore, the upper shift in G wavenumber and the decrease in I D / I G inform that sp 3 content of the film is directly proportional to DLC thickness. The plot modified from the three-stage model informed that the structural characteristics of DLC/a-Si bilayer films are located close to the tetrahedral amorphous carbon. This information may be important for analyzing and developing bilayer protective films for future hard disk drive.